2016
DOI: 10.1016/j.hpb.2016.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Risk by indication for pancreaticoduodenectomy in patients 80 years and older: a study from the American College of Surgeons National Surgical Quality Improvement Program

Abstract: Background: Expected mortality after elective pancreaticoduodenectomy (PD) in contemporary series is less than 5% in elderly patients; however, to our knowledge, mortality rate has not been correlated with indication for PD. We hypothesized that perioperative risk following PD would correlate with diagnostic indication in older patients. Methods:The American College of Surgeons NSQIP database was reviewed to identify patients (<80 and 80 years) who underwent PD from January 1, 2005, through December 31, 2012. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Recently, some authors have reported that elderly patients who underwent surgical resection for pancreatic cancer showed outcomes comparable to those shown by younger patients [19, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some authors have reported that elderly patients who underwent surgical resection for pancreatic cancer showed outcomes comparable to those shown by younger patients [19, 25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in past fast two decades have compared the mortality and morbidity among younger and elderly patients who underwent PD (3,(8)(9)(10)(11). In the majority of these studies, postoperative mortality and morbidity of older patients were slightly higher, but comparable to those of younger patients; however, the differences were significant in several large series (3,(8)(9)(10)(11). In the present study, compared to patients younger than 75 years, patients aged 75 years and over had a significantly higher mortality rate, with half of the deaths being infection-related, such as pneumonia and sepsis due to catheter infection.…”
Section: Discussionmentioning
confidence: 99%
“…This is basically independent of patient age [4]. The contribution of endoscopy with biopsy in case of malignancies with duodenal localization/invasion does not allow, in most cases, a clear differentiation between the two types of cancer.…”
Section: Introductionmentioning
confidence: 92%